Impact of BN and WC Particulate Reinforcements on Mechanical Properties and Damage Development of Al-2048 Metal Matrix Composites - T. Sivakumar; Chikkappa Udagani; M. Sivaranjani; M. Sudhakar; Reem Mohammed Alharbi; Neveen Abdel-Raouf; Ibraheem Borie M. Ibraheem; Essam Nageh Sholkamy; Mahadeo A. Mahadik; Simon Yishak (Advances in Materials Science and Engineering)
The primary goal of this work is to evaluate how BN and WC particles affect the mechanical properties and damage development behaviours of aluminum alloy-2048. Heat treatments for composites are also being investigated to improve mechanical properties. Tensile experiments reveal that BN particle reinforcement outperforms WC reinforcement in strength and flexibility for composites. T4 treatment, rather than traditional peak-aging treatment, is recommended for the composites (T6). The particle size distribution in 10v% WC/Al-2048 is the best in the three composites with the largest size of 16 µm and 80% of particles are from 6 to 10 µm. Tensile tests illustrate that 15v% BN/Al-2048 composite demonstrates a 9 and 14% rise in its ultimate tensile stress and 28 and 120% increases in its elongation. T4 heat treatment with an additional 0.6 percent prestrain can produce composites with the same UTS and 0.2 percent proof stress as T6 treatment, but the ultimate elongation below T4 treatment is over 100 percent more than that under T6 treatment. To make sense of the test results, an observation of the damage evolution behaviors of the reinforcing particles provides a concept that the composites’ strength is primarily determined by the balance between the reinforcing particles sharing the load and creating strain discontinuity in the matrix. The fraction of broken particles in the 20v% WC/Al-2048 composite as a function of strain is much higher than that in the 15v% BN/Al-2048 composite. Because of their tolerance for substantial strain at the interface, maximum K1c, and moderate thermal extension, BN elements can share a lot of loads and provide more excellent reinforcement than WC particles in terms of composite strength and flexibility.